PENGARUH DIAMETER TIANG TERHADAP TAHANAN GESEK TIANG DALAM TANAH LEMPUNG - Andikanoza Pradiptiya; A’isyah Salimah (Politeknik Negeri Jakarta, 2019)
AbstractSome buildings impose limits on the foundation displacement that occur with relatively small values so as not to cause structural damage. The test method used was to make a model test box as a testing medium by simulating the actual model into the form of a scale model. The study was conducted using a single pile foundation with reduced scale, made of concrete with a diameter of 0.02 m, 0.03 m, 0.04 m and the length of each pile was 0.4 m. The pile model was mounted by pressing into the clay that had been compacted in the test box and then given a tensile load which refers to ASTM D3689-07 procedure E (Constant Rate of Uplift Test). Mobilization of pile friction resistance at critical displacement determined the frictional resistance of the ultimate pile units. The test results showed that the greater the diameter of the pile, the frictional resistance of the ultimate pile units would increase. The increase in frictional resistance of the ultimate pile units showed an average value of around 17.1%.Keywords : Pile foundation, Pile diameter, Friction resistance.AbstrakMeningkatnya pembangunan hunian mengakibatkan naiknya permintaan akan batako, hal ini tentunya Beberapa konstruksi bangunan memberikan batasan kepada perpindahan tiang yang terjadi dengan nilai yang relatif kecil supaya tidak menyebabkan kerusakan struktur. Metode uji yang dipakai adalah membuat box uji model sebagai media pengujian, dengan mensimulasikan model yang sebenarnya ke dalam bentuk model skala. Penelitian dilakukan menggunakan model pondasi tiang tunggal penampang lingkaran lingkaran skala tereduksi yang terbuat dari beton dengan diameter 0,02 m, 0,03 m, 0,04 m dan panjang masing-masing tiang adalah 0,4 m. Model tiang dipasang dengan cara ditekan pada tanah lempung yang sudah dipadatkan dalam box uji kemudian diberikan beban tarik yang mengacu pada ASTM D3689-07 prosedur E (Constant Rate of Uplift Test). Mobilisasi tahanan gesek tiang pada perpindahan tiang kritis menetukan tahanan gesek satuan ultimit. Hasil uji memperlihatkan bahwa semakin besar diameter tiang, tahanan gesek satuan ultimit tiang akan bertambah. Peningkatan tahanan gesek satuan ultimit tiang menunjukkan rata-rata sekitar 17,1 %.Kata kunci : Pondasi Tiang, Diameter Tiang, Tahanan Gesek Tiang.